2022
DOI: 10.2196/40141
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Weight Loss Through Smartphone Apps: Systematic Review and Meta-analysis on Anthropometric, Metabolic, and Dietary Outcomes

Abstract: Background Evidence on the long-term effects of weight management smartphone apps on various weight-related outcomes remains scarce. Objective In this review, we aimed to examine the effects of smartphone apps on anthropometric, metabolic, and dietary outcomes at various time points. Methods Articles published from database inception to March 10, 2022 were searched, from 7 databases (Embase, CINAHL, PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 53 publications
1
18
0
1
Order By: Relevance
“…However, contrary to hypotheses, no significant differences were observed between groups over the study period. Taken together, the present study demonstrated that smartphone-delivered cognitive training that simulates interactions with healthy food stimuli undertaken in the free-living environment may elicit temporary attenuation of food reward and cravings, plausibly by inducing dietary self-monitoring or ostensible priming of healthy food choices (Chew et al, 2022).…”
Section: Discussionmentioning
confidence: 60%
“…However, contrary to hypotheses, no significant differences were observed between groups over the study period. Taken together, the present study demonstrated that smartphone-delivered cognitive training that simulates interactions with healthy food stimuli undertaken in the free-living environment may elicit temporary attenuation of food reward and cravings, plausibly by inducing dietary self-monitoring or ostensible priming of healthy food choices (Chew et al, 2022).…”
Section: Discussionmentioning
confidence: 60%
“…A recent meta-analysis reported that health apps can lead to a significant weight loss of up to 2.18 kg but little is known about the effects of an adjuvant health coaching element [ 34 ]. Our study found that the use of mobile apps in conjunction with a patient-centered health coaching program significantly improves weight loss (2.15 kg), WC, triglyceride, HbA 1c , and total calorie consumption per day as compared to usual care.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review indicates that mobile apps and related technology can positively affect health aspects, in particular weight loss, as well as diabetes prevention and treatment [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Similarly, an initial literature review indicates a significant number of publications on the use of Artificial Intelligence and Machine Learning techniques for diabetes prediction, prevention, and treatment [ 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Methodology and Contextual Approachmentioning
confidence: 99%